2021
DOI: 10.1177/0748730421997265
|View full text |Cite
|
Sign up to set email alerts
|

Nanda-Hamner Curves Show Huge Latitudinal Variation but No Circadian Components in Drosophila Montana Photoperiodism

Abstract: Insect species with a wide distribution offer a great opportunity to trace latitudinal variation in the photoperiodic regulation of traits important in reproduction and stress tolerances. We measured this variation in the photoperiodic time-measuring system underlying reproductive diapause in Drosophila montana, using a Nanda-Hamner (NH) protocol. None of the study strains showed diel rhythmicity in female diapause proportions under a constant day length (12 h) and varying night lengths in photoperiods ranging… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 46 publications
1
18
0
Order By: Relevance
“…D. montana females show no circadian rhythmicity (high diapause peaks in photoperiods with a length of 24 h or its multiples; Figure 2(b )) in their diapause proportions in NH experiments, which suggests that the PPTM of this species is either based on heavily damping circadian oscillator(s) or that it lacks strong oscillators [ 43 , 44 ]. NH experiments have also shown that D. montana females measure the night length quantitatively, that their photoperiodic counter may play a slightly different role in extra short and long photoperiods and that the northern strains of this species show high stability against perturbations in photoperiod length and in the presence of light: dark (LD) cycles [ 45 ], see Figure 2(b ). Accordingly, the function of PPTM in D. montana is best explained by the quantitative versions of the damped external coincidence model [ 45 ].…”
Section: Circadian Clock System and The Photoperiodic Timer Of The Virilis Group Species Show Unique Features That Arementioning
confidence: 99%
See 2 more Smart Citations
“…D. montana females show no circadian rhythmicity (high diapause peaks in photoperiods with a length of 24 h or its multiples; Figure 2(b )) in their diapause proportions in NH experiments, which suggests that the PPTM of this species is either based on heavily damping circadian oscillator(s) or that it lacks strong oscillators [ 43 , 44 ]. NH experiments have also shown that D. montana females measure the night length quantitatively, that their photoperiodic counter may play a slightly different role in extra short and long photoperiods and that the northern strains of this species show high stability against perturbations in photoperiod length and in the presence of light: dark (LD) cycles [ 45 ], see Figure 2(b ). Accordingly, the function of PPTM in D. montana is best explained by the quantitative versions of the damped external coincidence model [ 45 ].…”
Section: Circadian Clock System and The Photoperiodic Timer Of The Virilis Group Species Show Unique Features That Arementioning
confidence: 99%
“…NH experiments have also shown that D. montana females measure the night length quantitatively, that their photoperiodic counter may play a slightly different role in extra short and long photoperiods and that the northern strains of this species show high stability against perturbations in photoperiod length and in the presence of light: dark (LD) cycles [ 45 ], see Figure 2(b ). Accordingly, the function of PPTM in D. montana is best explained by the quantitative versions of the damped external coincidence model [ 45 ].…”
Section: Circadian Clock System and The Photoperiodic Timer Of The Virilis Group Species Show Unique Features That Arementioning
confidence: 99%
See 1 more Smart Citation
“…The more complex response in N. vitripennis , initially interpreted as evidence for internal coincidence, however, has been re-interpreted as evidence for oscillator dampening in a clock of the external coincidence type ( Saunders, 2021 )–but this requires further experimental investigation. In some species such as the aphid Megoura viciae ( Lees, 1986 ) and drosophilids from high latitudes such as Drosophila ezoana ( Vaze and Helfrich-Förster, 2016 ) and D. montana ( Lankinen et al, 2021 ) ‘negative’ NH responses, lacking peaks and troughs in diapause incidence, have been recorded. In these cases, PPTM resembles a non-circadian hourglass-like timer.…”
Section: Components Of the Circadian And Photoperiodic Systemsmentioning
confidence: 99%
“…In these cases, PPTM resembles a non-circadian hourglass-like timer. This hourglass-like clock mechanism, however, may be due to a rapidly dampening circadian oscillation, based upon the same molecular components as clocks showing ‘positive’ responses but with extreme reduction of their output ( Lewis and Saunders, 1987 ; Lankinen et al, 2021 ).…”
Section: Components Of the Circadian And Photoperiodic Systemsmentioning
confidence: 99%